OPTIMALISASI LAHAN PASANG SURUT PADA USAHATANI KEDELAI DI DESA ENGGAL REJO KECAMATAN AIR SALEH KABUPATEN BANYUASIN - Anisah, Khoirun; Batubara, Marli; Isakandar, Sutarmo (Universitas Muhammadiyah Palembang, 2015)
This study aims to determine the amount of income of soybean farming at Enggal Rejo village Air Saleh District Banyuasin regency and to determine whether optimization of tidal land on soybean farming in Enggal Rejo Village Air Saleh District Banyuasin regency is optimal.This research was conducted at the of Enggal Rejo village Air Saleh District Banyuasin regency in March until May 2015. Metode study is a survey method. While the sampling method used was simple random (Simple Random Sampling) with a population mamber as many 475. Then sample in as many as research 10% from population mamber that many as 48 farmers. Data collection methods used were interviews. Data collected consist of primary data and secondary data. Data processing and analysis methods were used that uses a mathematical model. To determine the amount of income used soybean income analysis and to optimize land on soybean used linear programming formulas. The results showed that the magnitude of the average income of soybean farming in Enggal Rejo village Rp -554.938/ha/MT. Soybean farm income shows a negative result means of soybean farming is experiencing a loss of acceptance obtained from soybean smaller than the production costs incurred in the production process of soybean farming.Furthermore, the results of the analysis to optimize land use program linear programming (LP), with a graphical method shows that acceptance is maximized (Z) lies in Z3 ie maximum reception on soybean Rp 14.111.937 / ha / MT. By optimizing the production of rice by 0.98 kg with total area of 1 hectare and soybean production optimization at 1.24 kg to 1 hectare land area. That is, the land is cultivated for soybean crops in Enggal Rejo village showed that the land has not been cultivated optimally.